En analys av vildrenars, fårs och kronhjorts nyttjande av saltstensplatser på norska fjäll i relation till avmagringssjuka (CWD) - Johansson, Cecilia (2021)
A common practice in Norway is to let sheep, goats and cattle roam freely in the mountains during summer. They are provided with salt licks, which is mainly done by farmers having sheep on summer pasture. Salt licks’ potential effect on spread of disease has been questioned in a larger context in Norway since 2016, when the first case of chronic wasting disease (CWD) was discovered in a population of wild reindeer. CWD is a prion disease that mainly affects deer, it spreads in the nervous system, it causes brain damage, emaciation and eventually death. The wild reindeer in Norway is the last of the population in Scandinavia and most of the whole population in northern Europe. It is important to understand their migration pattern and behaviours to understand the spread of the disease. This study was conducted to investigate the wild reindeer’s behaviours performed at the salt licks to evaluate the risk of being infected or spread CWD. Sheep, reindeer and red deer were part of the study to evaluate the overlap of habitat usage between the species, since this is believed to lead to interspecies transmission of CWD, even if the transmission routs need to be further investigated. By creating a machine learning model, this project analysed > 500 000 pictures from 34 camera traps in four different parts of the Norwegian highlands: Nordfjella, Dovrefjell, Knutshø and Forollhogna. The results showed that during the period May-October visits of wild reindeer, sheep and red deer overlapped at 27 of total 34 cameras. The behavioural study of reindeer made clear that they perform the behaviour grazing/head to the ground most frequent at the salt licks. It needs to be further investigated if removing the salt licks for sheep is an alternative for the future to stop spread of CWD and how that affects all animals in the highland.